Hodnotenie vybraných aspektov kurikulárnej reformy na gymnáziách v SR učiteľmi - Petra Fridrichová; Vladimír Poliach (Karolinum Press, 2018)
This paper focuses on the description of the course of curriculum reform in Slovakia in relation to the changes in secondary grammar schools ("gymnázium"). We offer an analysis of the selected aspects of the broader exploratory ex post facto research. We have analysed the data using MS Excel and IBM SPSS, mainly using nonparametric procedures, which resulted from the nature of the distribution of most variables. The results point to a negative perception of the direction of the Slovak education system by teachers after 1989. Teachers expect a comprehensive reform in education leading to minor changes in the content of education and fundamental changes in the teaching methods at secondary schools.